Cognition and Practice: Adult Learning Situated in Everyday Activity - Catherine A. Hansman; Arthur L. Wilson (Adult Education Research Conference, 1998)
Theories and procedures used to teach adults to write often lack an understanding of the central constitutive dimensions of activity, tools, and culture in adult learning. A situated view of teaching writing is introduced.